Amundsen Sea ice production and transport - Assmann, Karen M.; Hellmer, Hartmut H.; Jacobs, Stanley S. (Journal of Geophysical Research: Oceans, 2005)
Drift and variability of sea ice in the Amundsen Sea are investigated with ice buoys deployed in March 2000 and a coupled ice-ocean model. The Bremerhaven Regional Ice Ocean Simulations (BRIOS) model results are compared with in situ ocean, atmosphere, and sea ice measurements; satellite observations; and 8?19 months of buoy drift data. We identify a zone of coastal westward drift and a band of faster eastward drift, separated by a broad transition region characterized by variable ice motions. The model represents drift events at scales approaching its resolution but is limited at smaller scales and by deficiencies in the National Centers for Environmental Prediction forcing. Two thirds of the modeled ice production in the southern Amundsen moves westward near the coast, its transport modulated by meridional wind strength, damping sea ice formation in the eastern Ross Sea. Half of the ice exported from the Ross moves eastward into the northern Amundsen Sea, a net sea ice sink that also receives more than one third of the ice generated to its south. A low rate of exchange occurs with the Bellingshausen Sea, which must have a more independent ice regime. Snow ice formation resulting from high precipitation accounts for one quarter of the ice volume in the Amundsen Sea, aiding the formation of thick ice in a region with generally divergent ice drift. Freshwater extraction by sea ice formation is roughly balanced by precipitation and ice shelf melting, but a positive trend in the surface flux is consistent with an Amundsen source for reported freshening in the Ross Sea.
Keywords: Amundsenhavet; Rosshavet; Sørishavet; geofysikk; havis; oseanografi

Pioneer whalers in the Ross Sea, 1923–33 - Barr, William; Watt, James P C (Polar Record, 2005)
On Christmas Eve 1923, the whaling factory ship Sir James Clark Ross, commanded by Captain Carl Anton Larsen and accompanied by five catchers, reached the front of the Ross Ice Shelf; these were the first whaling vessels to operate in the Ross Sea. They had been dispatched by the Norwegian whaling company Hvalfangeraktienselskapet Rosshavet, which had obtained a licence from the British government. For most of the 1923–24 season, Sir James Clark Ross occupied an uneasy anchorage in the deep waters of Discovery Inlet, a narrow embayment in the front of the Ross Ice Shelf, while her catchers pursued whales widely in the Ross Sea. During that first season they killed and processed 221 whales (211 blue whales and 10 fin whales), which yielded 17,300 barrels of oil. During the next decade, with the exception of the 1931–32 season, Sir James Clark Ross and two other factory ships operated by Rosshavet, C.A. Larsen and Sir James Clark Ross II, operated in the Ross Sea. From the 1926–27 season onwards these ships were joined by up to three other factory ships and their catchers, operated by other companies. During the decade 1923–33 the Rosshavet ships killed and processed 9122 whales in the Ross Sea sector, mainly in the open waters of the Ross Sea south of the pack-ice belt. Total harvest for all factory ships from the Ross Sea sector for the period was 18,238 whales (mainly blue whales) producing 1,490,948 barrels of oil. From 1924 onwards the Rosshavet catchers wintered in Paterson Inlet on Stewart Island, New Zealand, and from 1925 onwards a well-equipped shipyard, Kaipipi Shipyard, operated on Price Peninsula in Paterson Inlet to service the Rosshavet ships.
Keywords: Carl Anton Larsen; Rosshavet; Sørishavet; hvalfangere; hvalfangstselskaper; pelagisk